Barriers and facilitators in delivering a new model of sexual health service for young people who are looked after - Hannah Dale; Lorna Watson (Scottish Journal of Residential Child Care)
The health of young people who are looked after away from home is frequently documented as poorer than their non-looked after peers (Polit et al., 1989; Buchanan, 1995; Meltzer et al., 2004). This includes the area of sexual health where these young people suffer even poorer outcomes and lower knowledge levels than their peers (Fraser, 2005; Department for Education and Skills, 2006). This is particularly concerning since, Scotland - and Fife in particular – tends to fare worse than most of Western Europe (Kmietowicz, 2002; Information Services Division, 2007; NHS, 2008; WHO, 2008). Many factors contribute to the poorer health of looked-after young people, including abuse, neglect, frequent change in placements, and poor adult role-modelling, along with a frequent history of socio-economic deprivation (Grant et al., 2002; Social Care Institute for Excellence, 2004; Scottish Healthy Care Network, 2007). Due to their poorer outcomes, the need to intervene with and prioritise them has often been highlighted (Scottish Executive, 2005; Scott & Hill, 2006; NHS Fife, 2007; Scottish Government, 2007; Health Scotland, 2008).